Value production of poplar clones - R. Petráš; J. Mecko; V. Nociar (Journal of Forest Science, 2008)
The results of research on the value production of the stands of poplar clones Robusta and I-214 carried out in Slovakia are presented. Models of value yield tables were constructed separately for each clone. The models simulate gross and net financial yield of wood production in dependence on the site index and age of stand. They were constructed on the basis of the models of assortment yield tables, timber prices according to assortments and the models of own costs of timber felling and processing. The clone I-214 produces a faster and higher proportion of thicker assortments of average and below-average quality, and therefore it has the higher value production at a younger age only. Robusta produces smaller diameter but higher quality assortments and has the higher value production only at an older age. The site index of the stand is the most important factor in the value production of poplar clones. Differences in the production between site indexes are much greater than between the clones.